2009
DOI: 10.1007/s11164-009-0026-8
|View full text |Cite
|
Sign up to set email alerts
|

Research on photodegradation of formaldehyde by nanocrystalline N-TiO2 powders under visible light irradiation

Abstract: The photo-degradation of formaldehyde (HCHO) by nitrogen-doped nanocrystalline TiO 2 (N-TiO 2 ) powders under visible light irradiation has been systematically investigated. Experimental results show that the degradation ratio reached up to 42.6% after 2 h visible light irradiation when the amounts of N-TiO 2 powders were 0.5 g, the initial concentration of the HCHO was set at 0.98 mg/m 3 , the illumination intensity was fixed at 10,000 lux, the ambient temperature was set at 26°C, and the relative humidity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…However, the influences of light intensity are seldom studied with visible light sources. The formaldehyde removal rates with N-doped TiO 2 photocatalyst were enhanced linearly form 25.5% to 59.6%, and stabilized thereafter, when the intensity increased to 30,000 lux with an initial concentration of 0.98 mg/m 3 [132].…”
Section: Removal Of Indoor Vocs and Formaldehyde Via Photocatalytimentioning
confidence: 99%
“…However, the influences of light intensity are seldom studied with visible light sources. The formaldehyde removal rates with N-doped TiO 2 photocatalyst were enhanced linearly form 25.5% to 59.6%, and stabilized thereafter, when the intensity increased to 30,000 lux with an initial concentration of 0.98 mg/m 3 [132].…”
Section: Removal Of Indoor Vocs and Formaldehyde Via Photocatalytimentioning
confidence: 99%
“…For visible light illuminated PCO reaction, the influence from light intensity is seldom discussed. Qu et al [45] studied the effect of visible light illumination on the photo-degradation of HCHO by a nitrogen doped TiO 2 photocatalyst. With HCHO initial concentration at 0.98 mg/m 3 (about 0.8 ppm at 20 ºC), the degradation increased linearly from 25.5% to 59.6% alongside an incrementing illumination intensity of 0-30,000 lux and stabilized thereafter.…”
Section: Effect Of Visible Light Intensitymentioning
confidence: 99%
“…During the gaseous PCO of VOCs, this nanostructured TiO 2 exhibited high activity and selectivity. Qu et al [13] reported a nitrogen-doped nanocrystalline TiO 2 (N-TiO 2 ) using the hydrothermal method. The N-TiO 2 powders exhibited good cycling performance and no obvious deactivation tendency for the photo-degradation of formaldehyde.…”
Section: Introductionmentioning
confidence: 99%